First observation of a doubly charged tetraquark and its neutral partner - Aaij, Roel; Archilli, Flavio; Bachmann, Sebastian; Borsato, Martino; Caspary, Rowina; Frau, Giulia; Günther, Paul André; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; Hu, Jiangqiao; Leverington, Blake; Li, Peilian; et al. (Physical review letters, 2023)
A combined amplitude analysis is performed for the decays B0→¯¯¯D0D+sπ− and B+→D−D+sπ+, which are related by isospin symmetry. The analysis is based on data collected by the LHCb detector in proton-proton collisions at center-of-mass energies of 7, 8, and 13 TeV. The full data sample corresponds to an integrated luminosity of 9 fb−1. Two new resonant states with masses of 2.908±0.011±0.020 GeV and widths of 0.136±0.023±0.013 GeV are observed, which decay to D+sπ+ and D+sπ− respectively. The former state indicates the first observation of a doubly charged open-charm tetraquark state with minimal quark content [c¯su¯d], and the latter state is a neutral tetraquark composed of [c¯s¯ud] quarks. Both states are found to have spin-parity of 0+, and their resonant parameters are consistent with each other, which suggests that they belong to an isospin triplet.
*LHCb Collaboration: R. Aaij, F. Archilli, S. Bachmann, M. Borsato, R. Caspary, G. Frau, P.A. Günther, X. Han, S. Hansmann-Menzemer, J. Hu, B. Leverington, P. Li, J. Marks, D.J. Unverzagt, U. Uwer, L. Witola, A. Zhelezov [und 1056 weitere Personen]
Gesehen am 31.01.2024